Theoretical Basis of the Green Infrastructure Strategy: International Experience - Maksymenko , N. V.; Burchenko, S. V. (Man and Environment. Issues of Neoecology, 2019)
The Green Infrastructure Strategy is used in different directions related to the design, protection and protection of the environment. Purpose. Analyze international experience in using the concept of green infrastructure, identify the main theoretical and practical approaches to assessing green infrastructure, analyze how to integrate green infrastructure strategies into territorial planning and integrate natural resources management in Europe and the world into policies. Methods. Literary search, analysis, synthesis, synthesis. Results. An analysis of scientific sources on the issue of studying the concept of green infrastructure; a review of the literature in related studies that directly or indirectly relate to the green infrastructure. It has been established that there are certain regional differences in the use of the concept of green infrastructure in Europe, America, and Asia. Directions of practical research in this area depend on the goals, functions and existing elements of the green infrastructure. As a result, its methodology can be modified. The possibilities and limitations of its use in Ukraine are revealed. The green infrastructure strategy has the greatest application in Europe and the USA to provide the ecological basis for the economic development of the territory. Now it is characterized as a development inward to greater detail, and in a spatial sense - covering all large areas. Conclusions. Given the lack of implementation mechanisms in Ukraine for the concept of green infrastructure, it is advisable to integrate it into landscape-ecological planning and recommend using it at the local level with subsequent spreading over large areas.